(untitled) (Alternautas, 2022)
Mining, right, to water, struggle, Amazon, Peru Since the 2008 financial crisis, increase in global demand and the price of gold have led to an expansion of industrial and artisanal gold mining (Swenson et al., 2011; World Gold Council, 2010). Worldwide, Artisanal and Small-Scale Gold Mining (ASGM) is carried out by an estimated number of 15 million miners in more than 70 countries (UNEP, 2015; Diringer et al., 2014) and accounts for 15 percent of the world gold production (Telmer, 2011). In Peru – which is currently the sixth largest gold producer in the world and the first in Latin America (Mujica, 2014) –, 70 percent of national artisanal gold production is mined in the department of Madre de Dios, located in the southwestern Amazon basin (Brooks et al., 2007). Since the 2000s commodities boom, Madre de Dios, considered one of the most biological places on the planet, has indeed experienced a rapid development of ASGM operations which have transformed large expanses of rainforests into denuded and mercury-poisoned wastelands (Asner et al., 2013; Elmes et al., 2014; Román et al., 2015). It is estimated that as many as 30.000 miners are working in this region (Fraser, 2009) and are using mercury to recover gold from the river sediments or solids extracted. Numerous studies show that mercury levels found in fishes and inhabitants of Madre de Dios are above the maximum levels recommended by the WHO (Damonte et al., 2015; Diringer et al., 2014; Ashe, 2012), therefore due to ASGM, artisanal miners as well as local population are exposed to dangerous levels of mercury contamination.